1980
DOI: 10.1287/opre.28.3.594
|View full text |Cite
|
Sign up to set email alerts
|

An Approximation Method for Open Restricted Queueing Networks

Abstract: This paper presents an approximation method for analyzing open restricted queueing networks with exponential service time and Poisson arrivals. Analysis is made by node-by-node decomposition through the introduction of a pseudo-arrival rate and an effective service rate. The method is applied to example networks and evaluated by comparing the results obtained thereby with those by simulations or exact calculations. We find that this method provides a fairly good approximation procedure for obtaining system per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(53 citation statements)
references
References 7 publications
2
50
0
1
Order By: Relevance
“…Hillier and Boling [9] is probably the first publication in this area. Since then, the method was further researched and extended by many publications [1,2,21,29]. Our study fundamentally applies the decomposition algorithm introduced by Takahashi et al [29], which dealt with blocking in an open queuing network system with feed-forward flows and finite buffers between stations.…”
Section: Methodoligical Background: Theory and Applicationmentioning
confidence: 99%
See 4 more Smart Citations
“…Hillier and Boling [9] is probably the first publication in this area. Since then, the method was further researched and extended by many publications [1,2,21,29]. Our study fundamentally applies the decomposition algorithm introduced by Takahashi et al [29], which dealt with blocking in an open queuing network system with feed-forward flows and finite buffers between stations.…”
Section: Methodoligical Background: Theory and Applicationmentioning
confidence: 99%
“…Our work, however, extends their model by modifying their single-server model to a multiple-server model. To author's knowledge, the direct application of Takahashi et al [29] in the context of multiple servers is only found in Korporal et al [15], which analyzed the congestion level in a penitentiary system in the Netherlands.…”
Section: Methodoligical Background: Theory and Applicationmentioning
confidence: 99%
See 3 more Smart Citations